2010
DOI: 10.17221/176/2009-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The influence of litter age, litter temperature and ventilation rate on ammonia emissions from a broiler rearing facility

Abstract: Broiler production is a prime example of high density animal production. Broilers are often grown in production houses containing 20 000 birds or more at densities of 0.06 m 2 per bird. Broiler litter typically contains 4 to 6 % nitrogen, much of which is in the NH 3 or NH 4 + form. The mixture of litter and manure is effectively a nitrogen storehouse. Under the proper conditions, a considerable quantity of this nitrogen will be released as ammonia (Carr et al., 1990). Many factors, such as season of the year,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 14 publications
2
17
1
2
Order By: Relevance
“…The elevated levels of ammonia in winter were attributed to the lower ventilation rate during cold weather. During the fattening period of broilers kept on renewed litter there is an average loss of 6.2 g ammonia per bird and/or 0.04 kg of ammonia per bird yearly (Knížatová et al, 2010c). Dolan et al (2013) found that at the average temperature and relative humidity 23.9 °C and 57.96%, respectively, in the hall and by the average 1.92 kg live body weight of birds (in 33rd day of fattening cycle) NH 3 production of 7.437 mg.kg…”
Section: Ammoniamentioning
confidence: 99%
“…The elevated levels of ammonia in winter were attributed to the lower ventilation rate during cold weather. During the fattening period of broilers kept on renewed litter there is an average loss of 6.2 g ammonia per bird and/or 0.04 kg of ammonia per bird yearly (Knížatová et al, 2010c). Dolan et al (2013) found that at the average temperature and relative humidity 23.9 °C and 57.96%, respectively, in the hall and by the average 1.92 kg live body weight of birds (in 33rd day of fattening cycle) NH 3 production of 7.437 mg.kg…”
Section: Ammoniamentioning
confidence: 99%
“…The influence of season on the Effect of the age and season of fattening period on carbon dioxide emissions from broiler housing M. Knížatová 1 , Š. Mihina 1,2 , J. Brouček 1 , I. Karandušovská 2 , G.J. Sauter 3 , J. Mačuhová amount of produced emissions is in fact the influence of ventilation rate, depending on the need to cool the temperature in the interior environment (Knížatová et al, 2010).…”
mentioning
confidence: 99%
“…Most poultry are grown on dirt floors with different bedding materials, which generally need to be very absorbent (to limit the production of ammonia and harmful pathogens) and must have a reasonable drying time [39][40][41].…”
Section: Poultrymentioning
confidence: 99%
“…Another type of house used in layer production is a single-story stair-step house. The cleaning frequency of both types of systems may be based on several factors: the quality of the manure or manure litter in the pit or in the house, the storage space remaining, or the integrator specified clean-out cycle [40][41][42][43][44][45][46][47][48][49][50]. Concentrations of harmful gases are commonly high in aviaries and floor housing systems in which manure is not regularly removed [51].…”
Section: Housing and Manure Managementmentioning
confidence: 99%
See 1 more Smart Citation